Epigenetic control of Epstein–Barr virus transcription – relevance to viral life cycle? - Sinclair, Alison J. (Frontiers in Genetics, 2013)
DNA-methylation normally leads to silencing of gene expression but Epstein-Barr virus (EBV) provides an exception to the epigenetic paradigm. DNA-methylation is absolutely required for the expression of many viral genes. Although the viral genome is initially unmethylated in newly infected cells, it becomes extensively methylated during the establishment of viral latency. One of the major regulators of EBV gene expression is a viral transcription factor called Zta (BZLF1, ZEBRA, Z) that resembles the cellular AP1 transcription factor. Zta recognizes at least 32 variants of a 7-nucleotide DNA sequence element, the Zta-response element (ZRE), some of which contain a CpG motif. Zta only binds to the latter class of ZREs in their DNA-methylated form, whether they occur in viral or cellular promoters and is functionally relevant for the activity of these promoters. The ability of Zta to interpret the differential DNA-methylation of the viral genome is paramount for both the establishment of viral latency and the release from latency to intiate viral replication.